Tracking Carbon Intensity of Global Container Fleet: Carbon Emissions Index (CEI) - Vukić, Luka (Transactions on Maritime Science, 2024)
With increasing pressure on the environment and the adoption of regulatory frameworks and policies aimed at reducing the carbon footprint of shipping, data-driven solutions are increasingly being deployed. This is particularly relevant for container shipping as it has inherently fixed liner services that correlate with the dominance of fuel costs in the overall cost structure, but also with the trends of overall capacity expansion and severe exogenous influences that contribute to supply chain disruptions. This paper presents the methodological background of the Carbon Emissions Index (CEI), a tool to measure the CO2 emissions of global container shipping companies and to validate the dynamics of change between available container trade routes. A comprehensive systematic analysis of the metrics and operational variables used in the algorithm is presented, as well as an overview of the practical application of CEI intensity and dynamics using the selected container trade routes. The results of this research highlight the role of digitalization in measuring the carbon footprint of container companies and the importance of reporting environmental performance through indices in shipping as an integral part of the contingent of performance metrics.